A SECONDARY SCHOOL TEACHER’S DESCRIPTION OF THE PROCESS OF DETERMINING REPORT CARD GRADES - Simon, Marielle; Robin, Tierney; Forgette-Giroux, Renée; Charland, Julie; Noonan, Brian; Duncan, Randy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
ABSTRACT. This paper presents a grade 10 mathematics teacher's in-depth description of the process she uses to determine the final grade for the report card within a standards-based context. Her case was part of a three-year comparative study of grading practices of teachers from two Canadian provinces that differ in their level of standardization of education. Survey, interview, and document data provided by the teacher revealed clear tensions between current grading policy and principles particularly within mathematics. DESCRIPTION PAR UNE ENSEIGNANTE DU SECONDAIRE DU PROCESSUS DE FIXATION DES RÉSULTATS AU BULLETIN RÉSUME. Dans cet article, une enseignante en mathématiques de secondaire 4 décrit en détails le processus par lequel elle détermine la note finale figurant au bulletin dans un contexte d'évaluation critériée. Son analyse fait partie d'une étude comparative de trois ans examinant les pratiques d'évaluation d'enseignants œuvrant dans deux provinces canadiennes dont les niveaux de normalisation de l'éducation diffèrent. Les données exposées par l'auteure - émanant de sondages, d'entrevues et de documents - mettent en évidence des tensions évidentes entre les politiques actuelles d'évaluation et les principes, particulièrement en ce qui a trait aux mathématiques.